2014
DOI: 10.1016/j.sbspro.2014.05.075
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Family Functioning and Dimensions of Parenting Style

Abstract: The systemic approach to family and the assumption that there is a correlation between patterns of family functioning and parenting styles are considered to be most appropriate when examining this problem. According to the Circumplex model proposed by Olson and his associates, balanced cohesion and flexibility are related to the democratic/authoritative parenting, which is the most desirable style from the standpoint of the developmental needs of a child. The aim of our study was to examine this assumption on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 7 publications
3
13
0
4
Order By: Relevance
“…The results are in line with the research by Matejevic, Todorovic and Jovanovic (2014) who, also on a sample of parents from Serbia, show that the authoritative parenting style is the dominant parenting style in the families of the students examined. The results are in line with research in other countries, as well (Waylen and Stewart-Brown, 2010;Yusuf and Sim, 2017).…”
Section: Table 1 Basic Parameters Of Parenting Stylessupporting
confidence: 91%
See 1 more Smart Citation
“…The results are in line with the research by Matejevic, Todorovic and Jovanovic (2014) who, also on a sample of parents from Serbia, show that the authoritative parenting style is the dominant parenting style in the families of the students examined. The results are in line with research in other countries, as well (Waylen and Stewart-Brown, 2010;Yusuf and Sim, 2017).…”
Section: Table 1 Basic Parameters Of Parenting Stylessupporting
confidence: 91%
“…Moreover, in that sense, there are differences in relation to child's autonomy. The possibility of this interpretation is confirmed by the results of the research, also in Serbia (Matejevic, Todorovic and Jovanovic, 2014), according to which autonomy had a higher arithmetic mean than regulation, but the respondents in that research were parents of adolescents.…”
Section: таBle 2 Basic Parameters Of Parental Styles' Dimensionsmentioning
confidence: 71%
“…However, the existing research only provided limited indirect evidence of the associations between parenting style and Zhongyong thinking. Specifically, a cross-sectional study of a sample of teenagers found that family function had a significantly positive relationship with the level of the individual's Zhongyong thinking (Yang, 2012), and parenting style was the main determinant of family functioning (Matejevic et al, 2014). Based on the above theoretical work and empirical studies, it is reasonable to infer that Zhongyong thinking style, an adaptive personality trait in Chinese culture, may also mediate the association between perceived parenting style and college student's emotional distress.…”
Section: The Mediating Role Of Zhongyong Thinkingmentioning
confidence: 99%
“…Family functioning usually has the characteristics of tendency towards stability and balance, the opportunity to adjust the situation, the existence of unity and the value of love and togetherness, and respect the differences of individuals which in turn create opportunities for individuals in the family to fulfill their role [9]. While socioemotional behaviour is a process that related to "changes in an individual's personality, emotions relationship with other people and social contexts" [10].…”
Section: Introductionmentioning
confidence: 99%